A new subspecies of the subgenus Ecdyonurus Eaton, 1868 (Ephemeroptera: Heptageniidae) from the East of Ukraine - Martynov, Alexander V.; Godunko, Roman J. (Zootaxa, 2013)
Ecdyonurus dispar gratificus ssp. nov. is reported from several small streams and rivers within the Donetsk Ridge (East of Ukraine). The new subspecies is described and illustrated on larvae and reared adults of both sexes. SEM photographs of the egg structures are presented. Critical diagnostic characters distinguishing the new subspecies from other represen-tatives of the subgenus Ecdyonurus Eaton, 1868 and especially from the nominal subspecies are discussed. The data on the biology and distribution are presented.